EFFECT OF YOGA ON CARDIORESPIRATORY PARAMETERSIN MEDICAL STUDENTS - DR CHANDRASHEKHAR DANGE; DR DNYANOBA DARADE; DR MRS SHUBHANGI DANGE (International Journal of Pharma and Bio Sciences, 2016)
In the changing scenario, stress is the part of human life. To this, medical students are no exception. Now a days, medical curriculum, is designed for examinations. Stress results from imbalance in the components of autonomic nervous system. Yoga is known to induce beneficial effects on physiological, biochemical and mental functions in man. Present study was undertaken to evaluate the physiological effects of yoga on the cardiorespiratory system.34 medical students were selected to undergo the session of yoga one hour per day to find out the effect of yoga on cardiorespiratory parameters. Yoga includes various asanas, suryanamaskar and pranayam. The parameters studied were pulse rate, blood pressure, respiratory rate, forced expiratory volume at the end of one second(FEV1), forced vital capacity (FVC), maximum ventillatory volume (MVV) and peak expiratory flow rate (PEFR). The results of this study showed marked improvement in cardio respiratory parameters after yoga session.